2011
DOI: 10.1103/physrevstab.14.030401
|View full text |Cite
|
Sign up to set email alerts
|

Electron acceleration by a radially polarized laser pulse during ionization of low density gases

Abstract: The acceleration of electrons by a radially polarized intense laser pulse has been studied. The axial electric field of the laser is responsible for electron acceleration. The axial electric field increases with decreasing laser spot size; however, the laser pulse gets defocused sooner for smaller values and the electrons do not experience high electric field for long, reducing the energy they can reach. The electron remains confined in the electric field of the laser for longer and the electron energy peaks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 38 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…In the past decades, as a typical kind of cylindrical vector beam with spatially non-unifrom state of polarization [1], radially polarized beam has been studied extensively in both theory and experiment due to its interesting and unique focusing properties, and has been found wide applications in microscopy, lithography, free space optical communications, electron acceleration, proton acceleration, particle trapping, material processing, optical data storage, high-resolution metrology, super-resolution imaging, plasmonic focusing, and laser machining [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Different methods have been developed to generate radially polarized beam [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, as a typical kind of cylindrical vector beam with spatially non-unifrom state of polarization [1], radially polarized beam has been studied extensively in both theory and experiment due to its interesting and unique focusing properties, and has been found wide applications in microscopy, lithography, free space optical communications, electron acceleration, proton acceleration, particle trapping, material processing, optical data storage, high-resolution metrology, super-resolution imaging, plasmonic focusing, and laser machining [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Different methods have been developed to generate radially polarized beam [1].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The electrons on the optical axis can be accelerated by the lowest order radially polarized Dark-Hollow Gaussian laser to the GeV energies because of the sizable longitudinal electric field. 18 The problem of acceleration of electrons in vacuum due to ponderomotive scattering effect has been studied by Hartemann et al 19 Malka et al have reported experimental results of electron acceleration to relativistic energies by the ultraintense linearly polarized laser pulse in vacuum. 14 In their experiment, they employed 20 (J) laser pulses with a wavelength of 1.056 (lm), pulse duration of 300 (fs), focal spot size 10 (lm), and peak intensity of 10 19 (W/cm 2 ) for an electron target in vacuum.…”
Section: Introductionmentioning
confidence: 98%
“…Radial polarization distributed beams can be used in particle acceleration [1,2], high-solution optical imaging systems [3], manipulation of particles [4] and laser machining [5]. Radial and azimuthal polarization distributed beams propagating through turbulent atmosphere have been investigated for further applications [6].…”
Section: Introductionmentioning
confidence: 99%